The Influence of Ethics, Whistleblowing System, and Management Pressure on Internal Auditor Performance - Ricky Bryan D.P. Tampubolon (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to empirically examine the influence of ethics, whistleblowing systems, and management pressure on the performance of internal auditors. Internal audit plays a critical role in strengthening governance, internal control, and fraud prevention. However, its effectiveness can be affected by ethical integrity, reporting mechanisms, and pressure from management. This research employed a quantitative approach using a survey method. Data were collected through questionnaires from 142 internal auditors in private companies based in Jakarta. The data were analyzed using multiple linear regression. The results reveal that ethics have a positive and significant effect on internal auditor performance, while management pressure has a significant negative effect. Conversely, the whistleblowing system does not significantly affect performance. These findings indicate that ethical awareness strengthens objectivity, accuracy, and transparency in audit processes. Meanwhile, excessive pressure from management can reduce independence and lead to compromised audit quality. The insignificance of the whistleblowing system suggests that trust in confidentiality and effectiveness of follow-up actions may still be lacking. This research emphasizes the importance of ethical training and the implementation of formal policies to protect auditors from undue pressure. Organizations are encouraged to improve the quality of their whistleblowing mechanisms to enhance audit effectiveness. Overall, ethics, whistleblowing systems, and management pressure collectively have a significant effect on internal audit performance.